2021
DOI: 10.1007/s10943-021-01235-4
|View full text |Cite
|
Sign up to set email alerts
|

Faith Communities’ Improvements in Readiness to Engage in Addictions Resilience and Recovery Support Programming

Abstract: Spirituality and religion are well-documented components of prevention, treatment and recovery of substance use disorders. Faith communities are in a distinct position to support recovery and resilience regarding substance use disorders—not only in times of crisis, but every day. We conducted an exploratory study of congregational (i.e., organizational) “levers” that can drive change readiness in implementing recovery and resilience programming for substance use disorders within faith communities. Findings poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This negative perception and stigma can come in many forms such as difficulty in getting job opportunities, not included in social events, and being blamed for any problems occurring in the community. Close emotional support such as family members and friends play an important role in buffering these negative experiences (Travis et al, 2021). This is because apart from the community, family and friends are the closest people to them.…”
Section: Emotional Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…This negative perception and stigma can come in many forms such as difficulty in getting job opportunities, not included in social events, and being blamed for any problems occurring in the community. Close emotional support such as family members and friends play an important role in buffering these negative experiences (Travis et al, 2021). This is because apart from the community, family and friends are the closest people to them.…”
Section: Emotional Supportmentioning
confidence: 99%
“…Next, faith communities have the potential to offer valuable emotional support through activities fostering a nurturing environment for addressing such challenges. A study by Travis et al (2021) found that groups of people who share faith can help others change their behavior, especially those struggling with addiction. After leaving a program to stop using drugs, people can feel lonely and alone.…”
Section: Emotional Supportmentioning
confidence: 99%